2020
DOI: 10.1002/ccr3.3369
|View full text |Cite
|
Sign up to set email alerts
|

Can COVID‐19 cause severe neutropenia?

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) produces a broad spectrum of respiratory symptoms, from mild to pneumonia and acute respiratory distress syndrome. Coronavirus disease (COVID-19) is associated with an inflammatory syndrome that may increase damage to the lungs. Several hematopoietic and hemostatic abnormalities have been described, as well as autoimmune disorders. 1,2 2 | CASE HISTORY We report a 33-year-old woman, a surgical nurse, with no relevant medical history (although her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 13 publications
(31 reference statements)
0
31
0
Order By: Relevance
“…4 López-Pereira et al have reported one case of acquired severe neutropenia, in a 33-year-old woman with no relevant medical history. 5 The patient presented with severe neutropenia (0.33×10 9 /L), asthenia and mild generalised lymphadenopathy 11 days after the COVID-19 diagnosis. She had no fever associated with neutropenia, and her neutrophil counts recovered after a single dose of G-CSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 López-Pereira et al have reported one case of acquired severe neutropenia, in a 33-year-old woman with no relevant medical history. 5 The patient presented with severe neutropenia (0.33×10 9 /L), asthenia and mild generalised lymphadenopathy 11 days after the COVID-19 diagnosis. She had no fever associated with neutropenia, and her neutrophil counts recovered after a single dose of G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed transient agranulocytosis occurring early in COVID-19 infection or peripheral neutrophil consumption as potential mechanisms of transient neutropenia. 5 Spencer et al reported a 51-year-old man with NK-cell large granular lymphocytic leukaemia who had stable pancytopenia on cyclosporine therapy and presented with febrile illness and worsening of neutropenia from baseline when he was diagnosed with COVID-19 infection; he was successfully managed with antibiotics and G-CSF. 6 Our patient had normal baseline leucocyte and neutrophil counts when he was hospitalised for COVID-19 infection, and he subsequently developed delayed-onset, transient, severe neutropenia together with neutropenic fever, around the fifth week of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with SARS-CoV-2 cannot be ruled out with certainty as another possible cause for the observed neutropenia, since new onset neutropenia has been reported previously in patients with SARS-CoV-2 infection. 21,22 In 1 case, discontinuation of the drug led to an improvement in absolute neutrophils count; however, in the other 2, such an improvement was not observed and the patients died. Obviously, rechallenge was not done in any of the patients.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike our patient, they chose to give their patient G-CSF to improve the neutrophil count. 9 We chose to wait to administer G-CSF to see if the patient would produce the appropriate neutrophil response without intervention, which he successfully did. This was done due to the high risk of potentially causing severe complications, to include potential cytokine storm and death.…”
Section: Discussionmentioning
confidence: 99%